Addressing Reading Instruction to the Issue of Essential Academic Achievements - Arina Mufrihah; Fitri Aulia (Journal of Education and Learning (EduLearn), 2017)
Oral presentation and reading skill were the academic success indicators of undergraduate students; however, the majority of students in their first semester encountered the reading-related problem and presentation-related problem. Thereby, aims of this study were to increase the reading skill of college students, involving them in constructing of new knowledge and improving their oral presentation skill. Classroom action research was the method of this study and Ebbut Cycle Model as the research design. Nineteen undergraduate students who were enrolled in the first semester participated as respondent and a variety of data were collected through observation, anecdotal record, interview, and the mark of assignment. In the last cycle, it could be asserted that nearly all of respondents could deliver the classroom presentation properly which was prepared from new knowledge construction and group discussion.